Implementing a task-based approach in teaching reading to third-year tourism-major students of the faculty of culture and tourism at Luong The Vinh University, Nam Dinh = Áp dụng phương pháp dạy học dựa trên nhiệm vụ trong việc dạy đọc hiểu cho sinh viên - Hoàng, Thị Hoa (ĐHNN, 2017)
44 p. + CD-ROM